2011
DOI: 10.1021/ci200446y
|View full text |Cite
|
Sign up to set email alerts
|

Library Enhancement through the Wisdom of Crowds

Abstract: We present a novel approach for enhancing the diversity of a chemical library rooted on the theory of the wisdom of crowds. Our approach was motivated by a desire to tap into the collective experience of our global medicinal chemistry community and involved four basic steps: (1) Candidate compounds for acquisition were screened using various structural and property filters in order to eliminate clearly nondrug-like matter. (2) The remaining compounds were clustered together with our in-house collection using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 59 publications
0
51
0
Order By: Relevance
“…Of the 685 compounds tested, 459 showed an EC 50 <4 µM, which underscores the inherent accuracy of the original screening data. A final collection of 400 were selected by a ‘wisdom of the crowd’ approach using experienced medicinal chemists [28].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 685 compounds tested, 459 showed an EC 50 <4 µM, which underscores the inherent accuracy of the original screening data. A final collection of 400 were selected by a ‘wisdom of the crowd’ approach using experienced medicinal chemists [28].…”
Section: Resultsmentioning
confidence: 99%
“…In particular we based the development of the QC metric on a crowd-sourced assessment of response matrix quality. The use of crowd-sourced assessments of “quality” and other abstract descriptors has precedents14151617. For example, Lajiness et al 18.…”
mentioning
confidence: 99%
“…Hack et al . reported an analogous study that sought to enhance the diversity of the Johnson & Johnson corporate structure database; they found that whilst there were considerable differences between individual chemists a fair level of consistency could be achieved using a wisdom-of-crowds approach [11]. This technique was also used by Oprea et al .…”
Section: Resultsmentioning
confidence: 99%